A national census of forensic in‐patients with intellectual disability and five‐year follow‐up. Issue 3 (19th December 2021) - Walker, Helen; Mann, Helen; Pitcairn, Jamie; Thomson, Lindsay
Abstract: A national census was undertaken for the first time to establish number of patients with ID in secure forensic in‐patient services in Scotland and identify their treatment needs. All forensic mental health units were identified and contacted with a request to contribute. Response rate was 100%. Initial results in 2013 revealed 89 patients with ID, 83 male and six female. This group contributes to 17% of the overall forensic in patient population ( n = 522). A higher proportion are from the North of Scotland. Key characteristics include an average age of 22 at first admission, history of violent offending, drug and alcohol abuse and self‐harm. Patients with ID in high secure services had significantly higher risk and total Historical Clinical Risk‐20 scores than those in a lower level. A range of significant health needs were identified enabling clinicians to build a profile of the population. A variety of medical, psychological and occupational interventions were utilised. Delivery seemed consistent across services, although poor recording made accurate assessment difficult. Nine percent were re‐admitted to a higher level of security within a 5‐year period (2013–2018). Repeated annual census findings revealed a slight decline in in‐patient numbers over a 5‐year period, although the proportion of ID patients (17%) remains constant. Data for 2018 indicate 85 people with ID, from a total in‐patient population of 490; female population increased to 10 (12%). Forty one (46%) patients either moved to a lower level of security or were discharged to community within a 5‐year period, indicating treatment success. This census provides unique evidence highlighting modest numbers of patients with ID, the majority of whom are cared for in low secure services. The populations' needs are considerable, but it is unclear if individual needs are being addressed. This requires further exploration, as does efficacy of interventions, in order to address the burden of psychological morbidity.